Perancangan Aplikasi Pemesanan Makanan Berbasis Mobile Hybrid Menggunakan Metode Waterfall - Asep Indrawan; Fajar Septian (CV. Multi Kreasi Media, 2024)
In general, restaurants are places that people visit to find a variety of food and drinks, and usually restaurants present their own uniqueness as an attraction, both through the menu, entertainment, and physical appearance of the building. Currently, there are still many restaurants that accept food orders on paper, one of which is Syasyaba Food Restaurant. This study aims to develop a mobile-based food and beverage ordering system and provide convenience for customers so that the process is faster and easier to get complete information, ranging from information about the available food and beverage menus to images, and improve the quality of restaurant service to consumers. The system design method used in this study is waterfall, which involves needs analysis, implementation design, and testing. It is hoped that the existence of this hybrid mobilebased food ordering application can make it easier for consumers to go through the process of ordering food and drinks at restaurants and be effective and easy for servant to see the orders that consumers want.